Beneficial use of hyperbranched polymer in cross‐linked anion exchange membranes for fuel cells. (23rd September 2022) - Cao, Kaiyue; Peng, Jinwu; Shan, Cengliang; Liu, Zhenchao; Liang, Minhui; Wang, Le; Hu, Wei; Liu, Baijun
Summary: A series of cross‐linked blend membranes based on a linear poly(2, 6‐dimethyl phenylene oxide) (PPO) and a hyperbranched poly(4‐vinylbenzyl chloride) (HVBC) are prepared via a simple solution casting procedure, followed by a cross‐linking treatment. The experiment indicates that the "HVBC enhancing PPO" membranes can have a looser cross‐linked "linear‐hyperbranched" blend structure, which is expected to improve the water absorption and dimensional stability. As a result, the excellent overall properties including high anion conductivity, low swelling, high strength, and excellent oxidative‐alkaline stability can be achieved simultaneously. A maximum conductivity of PPO‐HVBC‐100 (ion exchange capacity [IEC] 1.88 mmol/g) is up to 135.9 mS/cm at 80°C, which is 2.9 times higher than that of pristine PPO membrane (IEC 1.62 mmol/g). All the results reveal that the hyperbranched HVBC with a unique multi‐cation structure is a preferred "performance‐enhancing component" for the PPO‐based membranes, and this study also provides a novel idea for the preparation of high‐performance AEMs. Abstract : A series of cross‐linked blend membranes based on a linear poly(2, 6‐dimethyl phenylene oxide) (PPO) and a hyperbranched poly(4‐vinylbenzyl chloride) (HVBC) are prepared. The study indicates that the "HVBC enhancing PPO" membranes can have a looser cross‐linked "linear‐hyperbranched" blend structure, which is proved to be beneficial for the improvement of the overall properties including high anion conductivity, low swelling and high strength.